Perbaikan Sistem Pemenuhan Order untuk Pengaturan Muat di PT Sinar Sindra Pratama - Andrew Hermawan; Tanti Octavia (Jurnal Titra, 2014)
Sinar Sindra Pratama is one of ocean freight services for destination areas,such as NTT, Maluku, Borneo, and Irian Jaya. Sinar Sindra Pratama always improves its systems to satisfy their customers. The problems are customers’ arrival is not in line with the schedule and without notice. The purpose of this research is to improve the system of order fulfillment in this company. The proposed improvements are the system for confirmation and the system for receiving goods.